Análise de gerações e seleção de progênies superiores para produção de grãos em soja - Borges, Bruna Alves Mundim (2019)
The programs of genetic improvement of busbar or development of cultivars with high productive potential and aggregate favorable agronomic characters. In this regard, use genetic parameters such as monitoring parameters and selection gain tests, use the best guidelines of breeding programs. In this context, the objective of this work is to analyze the genetic and statistical parameters and select the superior genotypes that have the shortest cycle and the highest grain production. The present study was carried out at the Capim Branco experimental farm at the Federal University of Uberlândia and was subdivided into two experiments in which agronomic characters and grain production were interpreted for the segregated population F2 and backcrosses from the parents BMX Desafio RR and TMG 801. AA conduction of an F2 population, with their parents and backcrosses, was carried out in the field, with planting in a pit. From the selected data, it was possible to estimate genetic parameters that indicate variability for F2, RC1 and RC2. In addition, genetic gains were achieved by most of the characters analyzed, with emphasis on the number of days to maturation (NDM) with - 16.16% and grain production (PROD) with 154.27%. The superior genotypes regarding grain production were selected to generate the F3 population. The second experiment was carried out in the Uberlândia field, MG, in the 2018/2019 harvest, where 70 soybean F3 progenies were evaluated with the controls TMG 801 and BMX Desafio RR. The design used was that of complete randomized blocks with two replications in which agronomic characters and grain production were selected. There is a constant genetic variation for the characters NDM, NDR and PROD between the F3 progenies at the level and 1% by the F test. The direct selection for grain production in the F3 progenies provided an estimated selection gain of 47.49%. The use of the Mulamba & Mock (1978) selection index added a total reduction cycle and an increase in grain production, providing a selection gain of 38.10% for grain production. As progenies, UFU 9 and UFU 127 were superior in terms of grain production and presented semi-early cycles.